Presentation of the document: rules and regulations of the philharmonic society (2004)
The orchestra of the Philharmonic Society of Bogotá offered its first concert on January 5. 1847  after three months of intense preparation. Throughtout these months the rules and regulations of the society were composed and a handwritten copy survives, copied out by the Society's secretary, Domingo Antonio Maldonado. The rules and regulations were printed later on but the manuscript copy is a valuable historical document that contains the signatures of the founding members. The musician Andrés Martínez Montoya preserved this manuscript as well as the proceedings of the meetings of the early society. These documents allow us to view the genesis of the society.